Dana Jones, Physical and Hearing - Ralitsa Akins (Association of American Medical Colleges, 2011)
Abstract Introduction This objective structured clinical examination (OSCE) case was created for use with standardized patients (SPs), for teaching and/or evaluation purposes. Methods The case follows Dana Jones, a new patient coming in for a work physical. S/he is about to start working as a substitute teacher for the local school district, teaching middle school math and science. Dana's only complaint is that s/he recently started to miss hearing the doorbell and sometimes does not hear the phone ringing. Recommended length of the session is 15-45 minutes for the learner in the patient room, 10 minutes for the patient note (if required), and at least 30 minutes for debriefing with the faculty observer (for teaching purposes only). Results The case has been successfully implemented with 40 MS 1 students at the Texas Tech University Health Sciences Center Paul L. Foster School of Medicine. Interrater reliability was assessed on a continuous basis and, for 20 consecutive cases, was above 80%. Additionally, a case study was completed to review the interrater reliability between SPs and faculty observers in a multiple-station high-stakes OSCE examination; results indicated faculty and SPs matched in scoring. Discussion The case is intended for teaching/examination of medical students in years 1-4 (depending on a medical school's type of curriculum). The case could also be used for resident entry-level testing and faculty development in teaching.